GESTÃO DO CONHECIMENTO: UM ESTUDO SOBRE A RELAÇÃO ENTRE A LIDERANÇA TRANSFORMACIONAL, A CONVERSÃO DO CONHECIMENTO E A EFICÁCIA ORGANIZACIONAL - FOGANHOLO, Andre Luiz (2015)
This study aimed to analyze the relationship between Transformational Leadership, Knowledge Conversion and Organizational Effectiveness. There were considered theoretical assumptions concepts consolidated on the themes of this relationship, and recent research already carried out in other countries and organizational contexts. Based on this, it was identified potential exploratory study of a model that relates these three concepts. To this end, it is considered that organizations looking to achieve competitive advantage and incorporate the Knowledge-Based View, can achieve differentiation against its competitors. In this context, knowledge becomes more important and gains a leading role in these organizations. Thus creating knowledge through its employees happens to be one of the challenges on these organizations while suggesting improvement of its indicators on Economic, Social, Systemic and Political, which is defined by Organizational Effectiveness. Therefore, the conversion modes of knowledge in organizations, demonstrate relevance as it is created and transformed knowledge through interaction between existing knowledge of its employees. This conversion of knowledge or SECI model has four modes that are socialization, externalization, combination and internalization. From this perspective, leadership in organizations are presented as an element able to influence its employees through its style and thereby providing greater dynamic to the SECI model of knowledge conversion. It is identified then, in the leadership of transformational type, characteristics that may influence employees and therefore, it is understood that this relationship between Transformational Leadership and Knowledge conversion may have a positive influence on indicators of Organizational Effectiveness. Thus, this study sought to analyze a model to explore the relationship between the leadership of transformational type, Knowledge Translation (SECI) and the Organizational Effectiveness. This research was a quantitative approach to data collection through survey method, obtaining a total of 230 valid respondents from different organizations. The data collection instrument consisted of statements regarding the relationship model researched in a total of 44 items. The profile of respondents was concentrated between 30 and 39 years old, with a predominance of private organizations and IT departments / Telecom, Teaching and Human Resources respectively. Data analysis was by Exploratory Factor Analysis and Structural Equation Modeling via Partial Least Square Path Modeling (PLS-PM). As a result of this research analysis, hypotheses could be confirmed, concluding that the Transformational Leadership has positive influence on Knowledge conversion modes and; the Knowledge Conversion positively influences the Organizational Effectiveness. Still, it was concluded that the perception among respondents has no different result on the model of this research between those who own or no leadership role.